Pengaruh Social Media Marketing terhadap Kinerja Pemasaran Melalui Nilai Pelanggan (Studi kasus UMKM Kreatif di Kota Pontianak) - Lie Heng; Dewi Santika (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
The purpose of this research: (1) how social media marketing positively affects value creation capabilities, (2) how social media marketing has a positive effect on marketing performance, (3) how value creation capability positively affects marketing performance, and (4) how value creation capabilities mediate the relationship between social media marketing and marketing performance. The sample of this study amounted to 125 UMKM Kreatif actors in Pontianak. Sampling using non-probability sampling method and data collection method through questionnaire distribution. Researchers used the help of the Analysis of Moment Structure (AMOS) program version 24. This study found that social media marketing does not necessarily have a direct impact on improving marketing performance, social media marketing has an impact on value creation capabilities for customers, value creation capabilities affect marketing performance, and the mediating role of value creation capabilities that can drive the impact of social media marketing influence on improving marketing performance.